Contrast MR of the brain after high-perfusion cardiopulmonary bypass. - Simonson, T M; Yuh, W T; Hindman, B J; Embrey, R P; Halloran, J I; Behrendt, D M (American Journal of Neuroradiology, 1994)
PURPOSE To study the efficacy of contrast MR imaging in the evaluation of central nervous system complications in the cardiopulmonary bypass patient and attempt to explain their pathophysiology based on the MR appearance and the cardiopulmonary bypass protocol. METHOD Nineteen patients were prospectively studied with contrast MR examinations the day before and 3 to 7 days after cardiopulmonary bypass, to determine the nature, extent, and number of new postoperative MR abnormalities. Cardiopulmonary bypass parameters used in our institution included: membrane oxygenation, arterial filtration with a pore size of 25 microns, and a relatively high perfusion rate to produce a cardiac index of 2.0 to 2.5 L/min per m2. RESULTS The preoperative noncontrast MR examination showed age-related changes and/or signs of ischemia in 60% of patients on the day before surgery. However, there was no abnormal enhancement or new T2 abnormalities on any postoperative MR examination to suggest hypoperfusion or emboli. None of the 19 patients developed overt neurologic deficits postoperatively. Review of the cardiopulmonary bypass protocol used indicated significant variations in technique at different institutions. CONCLUSION Contrast MR imaging demonstrated no new abnormalities in patients after cardiopulmonary bypass performed with strict in-line arterial filtration and relatively high perfusion. MR imaging is feasible in the early postoperative period after cardiopulmonary bypass and may offer a convenient method for evaluation of the neurologic impact of technical factors associated with cardiopulmonary bypass.